Extension and Communication as a Medium to Raise Awareness for Millennial Farmers in Sleman Regency, Yogyakarta - Mahmuda, Luqman Abdulloh; Solikah, Umi Nur (Journal Management & Economics Review (JUMPER), 2025)
Agriculture is a sector that not only plays a role in providing food but also supports the national economy. However, this sector faces a major challenge in the form of declining interest among the younger generation in farming. The average age of farmers in Indonesia is currently relatively old, while the contribution of millennial farmers is still minimal. Sleman Regency, Yogyakarta Special Region, as one of the regional food barns, faces the same problem. Digital transformation actually opens up significant opportunities for the younger generation to play an active role in modern agriculture. However, limited knowledge, limited access to information, and negative perceptions that agriculture is less profitable are major obstacles. This study aims to analyze the role of extension and communication in raising awareness among millennial farmers in Sleman Regency. The research method used a qualitative descriptive approach with data collection techniques including in-depth interviews, participant observation, and documentation studies. Subjects included agricultural extension workers, young farmers aged 20–35, and agricultural community administrators. Data analysis was conducted using the Miles & Huberman model, including data reduction, data presentation, and conclusion drawing. The research results show that participatory communication-based extension services can increase the motivation, knowledge, and skills of millennial farmers in adopting modern agricultural technologies. Digital communication media, such as WhatsApp groups, Instagram, and YouTube, serve as effective channels for disseminating agricultural information, promoting products, and even learning techniques. The main obstacles encountered include limited internet access in some areas, inconsistent attendance at extension activities, and the social stigma that agriculture lacks promising prospects. In conclusion, face-to-face extension services combined with digital communication are effective strategies for building awareness and increasing engagement among millennial farmers in Sleman.